2003
DOI: 10.1177/0748730403259109
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Locomotor Activity in Solitary and Social Species of African Mole-Rats (Family: Bathyergidae)

Abstract: Mole-rats are strictly subterranean and hardly, if ever, come into contact with external light. As a result, their classical visual system is severely regressed and the circadian system proportionally expanded. The family Bathyergidae presents a unique opportunity to study the circadian system in the absence of the classical visual system in a range of species. Daily patterns of activity were studied in the laboratory under constant temperature but variable lighting regimes in individually housed animals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
92
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 19 publications
8
92
1
1
Order By: Relevance
“…Both species studied have a greatly reduced visual system (Oelschlager et al, 2000;Cernuda-Cernuda et al, 2003;Nemec et al, 2004), are subterranean, and appear to have a free-running circadian activity oscillator (Lovegrove and Papenfus, 1995;Lovegrove and Muir, 1996;Negroni et al, 2003;Oosthuizen et al, 2003;Gutjahr et al, 2004). These atypical rodent features combined with the distant (but familial) relation to each other and to the non-familial laboratory rat (Adkins et al, 2003), provide an interesting model to examine changes in nuclear organization and terminal network patterns that may be related to phenotype, life history and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Both species studied have a greatly reduced visual system (Oelschlager et al, 2000;Cernuda-Cernuda et al, 2003;Nemec et al, 2004), are subterranean, and appear to have a free-running circadian activity oscillator (Lovegrove and Papenfus, 1995;Lovegrove and Muir, 1996;Negroni et al, 2003;Oosthuizen et al, 2003;Gutjahr et al, 2004). These atypical rodent features combined with the distant (but familial) relation to each other and to the non-familial laboratory rat (Adkins et al, 2003), provide an interesting model to examine changes in nuclear organization and terminal network patterns that may be related to phenotype, life history and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that mole rats, subterranean, visually regressed rodents, have unusual patterns of circadian rhythmicity (Lovegrove and Papenfus, 1995;Lovegrove and Muir, 1996;Oosthuizen et al, 2003). Locomotor activity studies have shown that within a species of mole rat there are individuals that have a rhythmic chronotype, and others that are distinctly arrhythmic and this is seen in both social and solitary species of mole rat (Oosthuizen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Locomotor activity studies have shown that within a species of mole rat there are individuals that have a rhythmic chronotype, and others that are distinctly arrhythmic and this is seen in both social and solitary species of mole rat (Oosthuizen et al, 2003). A study of sleep patterns in the giant Zambian mole rat (Cryptomys mechowi) showed some differences in sleep patterns between rhythmic and arrhythmic chronotypes of this species, where arrhythmic individuals spend more time in waking with a longer average duration of a waking episode, and less time in nonREM (NREM) sleep with a shorter average duration of a NREM episode though with a greater NREM sleep intensity (Bhagwandin et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of this drumming breaks down territoriality between individuals and courtship is accompanied by increased testosterone levels (but see Oosthuizen and Bennett 2009) and enlargement of the testes and reproductive glands in males (Bennett 1988;Bennett et al 2006). Previous research on G. capensis has focused on its physiology (Oosthuizen et al 2003, Oosthuizen andBennett 2007;Oosthuizen et al 2008;Oosthuizen and Bennett 2009), reproductive biology (Taylor et al 1985;Bennett 1988;Bennett and Jarvis 1988;Kinahan et al 2008), intergeneric relationships (Honeycutt et al 1987;Nevo et al 1987;Allard and Honeycutt 1992;Faulkes et al 2004;Ingram et al 2004), age determination (Taylor et al 1985), seismic communication (Narins et al 1992), energetic cost of digging (Du Toit et al 1985; Scantlebury et al 2006), influence on plant communities (Hagenah and Bennett 2012) and burrowing dynamics (Romañach 2005;Thomas et al 2012). Invariably, sample sizes in these studies were small and biased towards single regions within the distributional range, especially the western Cape Province.…”
Section: Introductionmentioning
confidence: 99%